PERANCANGAN SISTEM ELEKTRONIK VOTING PENENTUAN PENGURUS OSIS MENGGUNAKAN PHP NATIVE (STUDI KASUS : SMK N 4 BATANGHARI): E-Voting, OSIS, PHP, Mysql. - Lisdarti; Hardianti, Siti (JURNAL AKADEMIKA, 2023)
In the world of education, information technology plays a very important role in supporting the teaching and learning process and supporting activities in schools, but not all activity processes have been accommodated by technological developments. The election system for the chairman and vice chairman of the OSIS at SMK Negeri 4 Batanghari still uses the conventional method. The voting process that is carried out is by ticking or punching on the ballot paper as a way of selecting candidates for the chairman and vice chairman of the OSIS. To overcome this, an application was built to carry out web-based voting or what is called e-voting (electronic voting). The evoting system is considered more effective and efficient in facilitating the vote counting process and the results of the election can be known quickly and accurately. In the process of making and designing an e-voting information system for the election of chairman and vice chairman of student council at SMK Negeri 4 Batanghari using the PHP programming language and using the MySql database, the author carried out system development with design analysis, system design, data flow diagrams.